Fluid mechanics - Kundu, Pijush K. (Academic Press, 2008)
Fluid mechanics, the study of how fluids behave and interact under various forces and in various applied situations-whether in the liquid or gaseous state or both-is introduced and comprehensively covered in this widely adopted text. Fully revised and updated with the addition of a new chapter on biofluid mechanics, Fluid Mechanics, Fourth Edition is suitable for both a first or second course in fluid mechanics at the graduate or advanced undergraduate level. The leading advanced general text on fluid mechanics, Kundu & Cohen's Fluid Mechanics, 4e now includes a free copy of the DVD "Mult.